REKONSTRUKSI PENGAKUAN LIVING LAW DALAM KUHP BARU DALAM PERSPEKTIF KEPASTIAN HUKUM PIDANA DI INDONESIA - Andri Andri; Edi Saputra Hasibuan; Marlina Samosir (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study examines the reconstruction of the recognition of living law in society (living law) in the National Criminal Code (KUHP) and its implications for the principle of criminal legal certainty in Indonesia. The recognition of living law through Article 2 of Law Number 1 of 2023 marks a paradigm shift from absolute legal positivism to inclusive legal pluralism. However, the integration of unwritten law into the codified criminal system poses serious challenges to the principle of formal legality (nullum crimen sine lege scripta). The research method used is normative juridical with a conceptual approach and the legislation of the new Criminal Code. The results of the study indicate that the recognition of living law requires juridical reconstruction in the form of codification of customary norms into Regional Regulations (Perda) as a requirement to fulfill the aspect of legal certainty. Without clear parameters regarding the types of sanctions and the territorial boundaries of its application, this recognition has the potential to trigger legal discrimination and uncertainty for legal subjects. This study concludes that synchronizing local justice values with national human rights standards is key to the successful implementation of living law in a modern legal system.